Virulent Variants Emerging in Mice Infected with the Apathogenic Prototype Strain of the Parvovirus Minute Virus of Mice Exhibit a Capsid with Low Avidity for a Primary Receptor - Rubio, Mari-Paz (American Society for Microbiology, 2005)
The mechanisms involved in the emergence of virulent mammalian viruses were investigated in the adult immunodeficient SCID mouse infected by the attenuated prototype strain of the parvovirus Minute Virus of Mice (MVMp). Cloned MVMp intravenously inoculated in mice consistently evolved during weeks of subclinical infection to variants showing altered plaque phenotypes. All the isolated large-plaque variants spread systemically from the oronasal cavity and replicated in major organs (brain, kidney, liver), in sharp contrast to the absolute inability of the MVMp and small-plaque variants to productively invade SCID organs by this natural route of infection. The virulent variants retained the MVMp capacity to infect mouse fibroblasts, consistent with the lack of genetic changes across the 220-to-335 amino acid sequence of VP2, a capsid domain containing main determinants of MVM tropism. However, the capsid of the virulent variants shared a lower affinity than the wild type for a primary receptor used in the cytotoxic infection. The capsid gene of a virulent variant engineered in the MVMp background endowed the recombinant virus with a large-plaque phenotype, lower affinity for the receptor, and productive invasiveness by the oronasal route in SCID mice, eventually leading to 100% mortality. In the analysis of virulence in mice, both MVMp and the recombinant virus similarly gained the bloodstream 1 to 2 days postoronasal inoculation and remained infectious when adsorbed to blood cells in vitro. However, the wild-type MVMp was cleared from circulation a few days afterwards, in contrast to the viremia of the recombinant virus, which was sustained for life. Significantly, attachment to an abundant receptor of primary mouse kidney epithelial cells by both viruses could be quantitatively competed by wild-type MVMp capsids, indicating that virulence is not due to an extended receptor usage in target tissues. We conclude that the selection of capsid-receptor interactions of low affinity, which favors systemic infection, is a major evolutionary process in the adaptation of parvoviruses to new hosts and in the cause of disease.